The Role of Leadership and Organizational Culture towards Increasing the Visitor Satisfaction in the Greek Museums - Kopsidas , Odysseas; Maska , Laura; Zacharioudakis , Nikolaos Christos (Journal of Ecohumanism, 2024)
The goal of this paper is to determine how Leadership and Organizational Culture can positively affect Visitor Satisfaction in the museums of Athens, Greece in the midst of a serious financial crisis. The clear objectives of this study are: firstly, to assess the impact of the different types of Leadership on Visitor Satisfaction in Greek Museums. Secondly, to determine how important is Organizational Culture in terms of influencing Visitor Satisfaction in Greek Museums, furthermore, to analyze the combined effects, if any, of Leadership and Organizational Culture on Visitor Satisfaction. The survey utilized both qualitative and quantitative types of research and was separated in three parts. Leadership and Visitor Satisfaction were analyzed with quantitative means, with leadership questionnaires being distributed to museum employees for the assessment of each museum’s leadership style, while, visitor satisfaction questionnaires were dispatched to museum visitors asking them what their experience from the museum they had just visited was along with which are, according to their personal opinion, the most important features of a “perfect” museum. On the other side of the spectrum, organizational culture was examined through qualitative means, more specifically interviews, in which nine museum employees were asked their personal opinion concerning notions based on museum culture theories. As far as visitor satisfaction is concerned a clear bottom-line was drawn, with straight forward conclusions as to which factors are the most important for highly satisfied visitors.